Does domain-general auditory processing uniquely explain the outcomes of second language speech acquisition, even once cognitive and demographic variables are accounted for?. Issue 5 (27th November 2022) - Saito, Kazuya; Cui, Haining; Suzukida, Yui; Dardon, Diego Elisandro; Suzuki, Yuichi; Jeong, Hyeonjeong; Révész, Andrea; Sugiura, Motoaki; Tierney, Adam
Abstract: Extending the paradigm in L1 acquisition, scholars have begun to investigate whether participants' domain-general ability to represent, encode, and integrate spectral and temporal dimensions of sounds (i.e., auditory processing) could be a potential determinant of the outcomes of post-pubertal L2 speech learning. The current study set out to test the hypothesis that auditory processing makes a unique contribution to L2 speech acquisition, for 70 Japanese classroom learners of English with different levels of L2 proficiency when biographical backgrounds (length of instruction and immersion) and memory abilities (working, declarative, and procedural memory) are controlled for. Auditory processing loaded onto modality-general capacities to represent and incorporate anchor stimuli (relative to target stimuli) into long-term memory in an implicit fashion, but dissociated from explicit abilities to remember, associate, and elaborate sensory information. Auditory processing explained a small-to-medium amount of variance in L2 speech learning, even after the other potentially confounding variables were statistically factored out.